Sound source localization is a multisystem process - Yost, William A.; Dorman, Michael F.; Pastore, M. Torben (Acoustical Science and Technology, 2020)
A review of data published or presented by the authors from two populations of subjects (normal hearing listeners and patients fit with cochlear implants, CIs) involving research on sound source localization when listeners move is provided. The overall theme of the review is that sound source localization requires an integration of auditory-spatial and head-position cues and is, therefore, a multisystem process. Research with normal hearing listeners includes that related to the Wallach Azimuth Illusion, and additional aspects of sound source localization perception when listeners and sound sources rotate. Research with CI patients involves investigations of sound source localization performance by patients fit with a single CI, bilateral CIs, a CI and a hearing aid (bimodal patients), and single-sided deaf patients with one normal functioning ear and the other ear fit with a CI. Past research involving CI patients who were stationary and more recent data based on CI patients' use of head rotation to localize sound sources is summarized.